Development of a Validated LC-MS Method for the Determination of Cannabinoids and Evaluation of Supercritical CO2 vs. Ultrasound-Assisted Extraction in Cannabis sativa L. (Kompolti cv.) - Vasileios A. Ioannidis; Varvara Sygouni; Sotirios Giannopoulos; Konstantinos Sotirianos; Theophilos Ioannides; Christakis A. Paraskeva; Fotini N. Lamari (Antioxidants, 2025)
Cannabis (Cannabis sativa L.) contains numerous secondary metabolites with different bioactivities. Extraction methods differ in their efficiency in recovering metabolites from plant material, and thus cannabis extracts vary significantly in their composition and activity. We aimed to develop a repeatable and accurate HPLC-MS method for the determination of nine common cannabinoids and compare two widely used extraction techniques: ultrasound-assisted extraction (UAE) with methanol and supercritical CO2 extraction (SFE). Inflorescences of the Kompolti cultivar were used as the plant material. On a polar C18 column, more than thirty compounds were well separated within 25 min; thirteen cannabinoids were identified and eight of them were quantified, with cannabidiol and its acidic precursor being the most abundant. Additionally, three spectrophotometric assays were employed for extract characterization: the total phenolic content, total flavonoid content, and DPPH radical scavenging capacity. The SFE extract, obtained using ethanol as a co-solvent under low pressure (<100 bar) and temperature (<45 °C), was more enriched than the UAE extract (181.62 ± 2.90 vs. 140.64 ± 13.24 mg quercetin equivalents/g of dry extract) and cannabinoids (446.29 ± 22.66 vs. 379.85 ± 17.16 mg/g of dry extract), especially cannabinoid acids. However, UAE achieved greater recovery from the plant material (cannabinoids: 83.42 ± 5.15 vs. 68.84 ± 3.49 mg/g of plant material) and showed superior antioxidant capacity (DPPH IC50: 2.50 ± 0.18 vs. 3.37 ± 0.07 mg/mL). Notwithstanding the observed partial decarboxylation, the high repeatability (RSD < 15%, n = 11) of the entire analytical workflow involving UAE extraction and LC-MS analysis renders it suitable for routine analyses. This study contributes to the ongoing efforts toward the quality control and valorization of C. sativa.